An analytical look at Al-Fusul wa Al-Gghayat by Abul Ala Al-Maarri - Ali Ganjiyan; Abdolahad Gheibi; Farshid Farajzadeh (دراسات في اللغة العربيّة وآدابها)
Abul Ala Al-Maarri has left a remarkable inheritance of his writings and compositions. Al-Fusul wa al-ghayat is one of his most important prose works that is viewed as a worthy source in the history of Arabic literature. The present article aims to investigate this book regarding its form and content. Rhythm, harmony, imagination, terms, sentences, rhetorical style, design and structure are the subjects which are going to be examined with respect to their formal usage. Moreover, admiration and compliment of the wise and admiration of the unwise are the issue which will be examined with regard to the content. Considering some of the critics who believe that Abul Ala authored this book in disapproval and opposition of the Quran, this study attempts to cleanse the dust of accusation from the face of this book by providing some reasons and proofs.